2017
DOI: 10.1007/s00125-017-4329-9
|View full text |Cite
|
Sign up to set email alerts
|

The kynurenine:tryptophan ratio as a predictor of incident type 2 diabetes mellitus in individuals with coronary artery disease

Abstract: Aims/hypothesisThe tryptophan metabolite kynurenine has potent immune modulatory and vasoactive properties. Experimental data implicate kynurenine in obesity-related morbidities. Epidemiological studies are, however, sparse. We evaluated associations of the plasma and urine kynurenine:tryptophan ratio (KTR) to incident type 2 diabetes.MethodsWe followed 2519 individuals with coronary artery disease (CAD; 73.1% men) without diabetes at baseline for a median of 7.6 years, during which 173 (6.9%) new incidences o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 47 publications
1
53
2
Order By: Relevance
“…Enzyme expression was greatest in activated macrophages, consistent with the finding that pathway activation could be induced in adipocytes by pro-inflammatory cytokines. There is strong evidence implicating the kynurenine pathway in the ‘metabolic syndrome’ and insulin resistance which is one of its major features in many obese individuals ( Filho et al, 2018 ; Oh et al, 2017 ; Oxenkrug et al, 2017 ; Rebnord et al, 2017 ). There is a clear correlation between plasma levels of tryptophan and its metabolites, leptin and BMI ( Samad et al, 2017 ).…”
Section: New Conceptsmentioning
confidence: 99%
“…Enzyme expression was greatest in activated macrophages, consistent with the finding that pathway activation could be induced in adipocytes by pro-inflammatory cytokines. There is strong evidence implicating the kynurenine pathway in the ‘metabolic syndrome’ and insulin resistance which is one of its major features in many obese individuals ( Filho et al, 2018 ; Oh et al, 2017 ; Oxenkrug et al, 2017 ; Rebnord et al, 2017 ). There is a clear correlation between plasma levels of tryptophan and its metabolites, leptin and BMI ( Samad et al, 2017 ).…”
Section: New Conceptsmentioning
confidence: 99%
“…Using these criteria, a total of 3344 eligible individuals were included in the final analyses. Individuals with incident diabetes during the followup were identified from the Norwegian prescription database, hospital discharge diagnosis and WENBIT trial follow-up, as previously described in detail [13]. Because information on incident diabetes was collected through 31 December 2009, i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Preventing diabetes might be a pathway by which IDO1 lowers the risk of IHD. Previous studies of IDO1 and type 2 diabetes are limited, although some have suggested diabetes up-regulates the tryptophan-kynurenine pathway 36,37 . Given IDO1 has complex and multiple functionality 7,38 , its effects on type 2 diabetes as well as the underlying mechanism, such as via insulin given products of the kynurenine pathway inhibit the synthesis and activity of insulin 39 , needs further investigation.…”
Section: Discussionmentioning
confidence: 99%